2021
DOI: 10.1088/1757-899x/1054/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Textile Waste as an Addition in the elaboration of an Ecological Concrete Block

Abstract: The textile industry has grown significantly in recent years, reaching a global fiber production of 53 million tons which 12 % are recycled; Construction sector has been using more and more recycled materials from different industrial sources, to apply them in their constructions and to reduce CO2 emissions and final energy consumption. The present study aims to study the behavior of concrete blocks of f´c = 210 kg/cm2 adding polyester textile waste with 3 %, 6 %, 9 %, 12 % and 15 %; void content, compressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Anglade et al [29] found that concrete blocks with polyester textile waste were superior thermal insulators. Tran et al [30] have investigated concrete reinforced with nylon or polypropylene carpet fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Anglade et al [29] found that concrete blocks with polyester textile waste were superior thermal insulators. Tran et al [30] have investigated concrete reinforced with nylon or polypropylene carpet fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed an increased energy absorption and flexural strength of concrete with cloth content from 1 to 5%. Increases in acoustic insulation and decreases in compressive strength were observed by Anglade et al [12] for concrete with polyester fabric (30 mm × 60 mm, thickness of 2 mm). Patnaik et al [13] discovered that the thermal conductivity of waste with 100% recycled polyester fiber is 9.4% higher than waste with 100% woolen, and the thermal conductivity is also decreased.…”
Section: Textile Wastes In Concretementioning
confidence: 73%
“…Textile waste materials are used by the furniture, carpet, paper, textile, automotive and construction industries [56]. There are studies available in the literature on the use of textile waste as fillers to produce composite materials, including partition walls [57], ceiling tiles [58], acoustic panels [59,60], thermal insulating materials [61,62], cement mortars [63] and as an addition to concrete [64,65].…”
Section: Introductionmentioning
confidence: 99%